2019
DOI: 10.2174/1573405614666180425142141
|View full text |Cite
|
Sign up to set email alerts
|

Nodule Size Effect on Diagnostic Performance of Ultrasonography and Computed Tomography for Papillary Thyroid Carcinoma

Abstract: Background: To compare the abilities of ultrasonography (US) and Computed Tomography (CT) to identify calcifications and to predict probability of malignancy for Papillary Thyroid Carcinoma (PTC) and Papillary Thyroid Microcarcinoma (PTMC). Methods: We reviewed 1008 cases of PTC/PTMC with calcifications reported by pre-operative US, CT, or post-operative pathology. The size of the thyroid nodule was obtained from the US report and the maximum diameter (d) was documented. According to the nodule size (d), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Ideally, another examination means is performed before a SMI examination is carried out, and then a comprehensive assessment result is offered. The findings of Li et al 20 show: the detection rates of conventional ultrasound and SMI decrease with the reduction of nodules, while CT is superior over ultrasound for small nodules. Traylor et al 21 believe that CT imaging is very important for preoperative evaluation of thyroid masses and thyroid cancers, while CT should be used as an important auxiliary means of SMI.…”
Section: Discussionmentioning
confidence: 97%
“…Ideally, another examination means is performed before a SMI examination is carried out, and then a comprehensive assessment result is offered. The findings of Li et al 20 show: the detection rates of conventional ultrasound and SMI decrease with the reduction of nodules, while CT is superior over ultrasound for small nodules. Traylor et al 21 believe that CT imaging is very important for preoperative evaluation of thyroid masses and thyroid cancers, while CT should be used as an important auxiliary means of SMI.…”
Section: Discussionmentioning
confidence: 97%
“…Zheng et al have reported that clinical characteristics and sonographic features were helpful for diagnosis of PTL and diffuse sclerosing variant of papillary thyroid carcinoma (DSVPTC) before surgery [15]. The treatment for PTL is mainly chemotherapy and radiotherapy, with not so expected benefit of surgical resection [2,16], while surgery is the preferred treatment for PTC [17,18]. High frequency ultrasonography is the first choice of thyroid disease examination [19,20], and studies [5,21] have shown that CT is a supplementary diagnostic technique for thyroid diseases, due to its advantages in determining the location and range of tumors as well as its superiority to ultrasound in evaluating the infiltration range.…”
Section: Introductionmentioning
confidence: 99%
“…PTL and PTC differ in the therapeutic method, although they are both thyroid malignancies. The treatment for PTL is mainly chemotherapy and radiotherapy, with not so expected bene t of surgical resection [2,8], while surgery is the preferred treatment for PTC [9,10]. High frequency ultrasonography is the rst choice of thyroid disease examination [11,12], and studies [5,13] have shown that CT is a supplementary diagnostic technique for thyroid diseases, due to its advantages in determining the location and range of tumors as well as its superiority to ultrasound in evaluating the in ltration range.…”
Section: Introductionmentioning
confidence: 99%